2016
DOI: 10.7717/peerj.2798
|View full text |Cite
|
Sign up to set email alerts
|

Preventative and therapeutic effects of a GABA transporter 1 inhibitor administered systemically in a mouse model of paclitaxel-induced neuropathic pain

Abstract: BackgroundThere is a dearth of drugs to manage a dose-limiting painful peripheral neuropathy induced by paclitaxel in some patients during the treatment of cancer. Gamma-aminobutyric acid transporter-1 (GAT-1) whose expression is increased in the brain and spinal cord during paclitaxel-induced neuropathic pain (PINP) might be a potential therapeutic target for managing PINP. Thus, our aim was to evaluate if systemic administration of a GAT-1 inhibitor ameliorates PINP.MethodsThe reaction latency to thermal sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Thermal sensitivity was assessed using the hot or cold plate (Panlab SL, Barcelona, Spain) at 55 ± 1 • C or 4 ± 1 • C, as described before [12,92,93]. Briefly, each mouse was placed individually in a hot or cold plate, and the first sign of nociception, paw licking, flinching or jump response to avoid the heat or cold was recorded and the animal immediately removed from the plate.…”
Section: Assessment Of Response To Thermal Stimulimentioning
confidence: 99%
“…Thermal sensitivity was assessed using the hot or cold plate (Panlab SL, Barcelona, Spain) at 55 ± 1 • C or 4 ± 1 • C, as described before [12,92,93]. Briefly, each mouse was placed individually in a hot or cold plate, and the first sign of nociception, paw licking, flinching or jump response to avoid the heat or cold was recorded and the animal immediately removed from the plate.…”
Section: Assessment Of Response To Thermal Stimulimentioning
confidence: 99%
“…Decreased GABAergic neurotransmission due to excessive IL-17 levels in the spinal cord has been linked to CIPN caused by paclitaxel [171], and the inhibition of GABA reuptake with by NO-711, a selective GABA transporter isoform 1 (GAT-1) inhibitor [172], prevents the development of thermal hyperalgesia and allodynia in paclitaxel-treated mice. NO-711 is also therapeutically effective for pre-existing CIPN [173]. Also, GABAergic precursor cell transplants reverse paclitaxel-induced mechanical hypersensitivity [174].…”
Section: Central Nervous System Structures and Neurotransmittersmentioning
confidence: 99%
“… 64 During PIPN in rodents, dysregulation of the γ-aminobutyric acid (GABA) neurotransmitter system, which is involved in the pathogenesis of neuropathic pain, was confirmed in the ACC via observing a significant increase in gene expression of GABA transporter-1 (GAT-1). 62 , 63 GAT-1 is the major transporter responsible for GABA uptake from the synapses in the brain. It has been confirmed that blockage of GAT-1 ameliorated PIPN, indicating a significant role of GAT-1 in the pathophysiology of PIPN.…”
Section: Pathology Of Pipnmentioning
confidence: 99%